Lipase-PDA-TiO2 NPs: An emphatic nano-biocatalyst for optimized biodiesel production from Jatropha curcas oil. (May 2021) - Zulfiqar, Anam; Mumtaz, Muhammad Waseem; Mukhtar, Hamid; Najeeb, Jawayria; Irfan, Ahmad; Akram, Sadia; Touqeer, Tooba; Nabi, Ghulam
Abstract: Current study was designed for developing the novel nano-biocatalyst (Lipase-PDA-TiO2 NPs) for enzymatic transesterification of Jatropha curcas seed oil (JCSO). The TiO2 NPs were prepared by the hydrothermal method and were afterward modified by the polydopamine (PDA) polymer. The synthesized nanomaterial was characterized by SEM, FTIR, XRD and energy dispersive X-ray spectroscopy. Lipase activity assay was used to check the stability of immobilized enzyme under varying conditions of pH and temperature. Transesterification of JCSO using Lipase-PDA-TiO2 NPs catalyst was optimized by response surface methodology (RSM). Optimum biodiesel yield (92%) was achieved by carrying out the transesterification process for 30 h at 37 °C temperature with 10% nano-biocatalyst concentration, 6:1 methanol:oil ratio and 0.5% water content. On the basis of model significance, R 2 value, lack of fit test and predicted vs. actual values, quadratic model was selected as the best fitted model. The FTIR technique was utilized to monitor the transesterification process. The comparison of the physiochemical characteristics of the synthesized biodiesel with the international standard for bio-fuel affirms that the transesterification of JCSO in the presence of the nano-biocatalyst provides an effective alternative for the production of biodiesel. Graphical abstract: Image 1 Highlights: TiO2 nanoparticles were prepared through hydrothermal method. NP surface was modified with PDA followed by lipase immobilization. 82.56% initial lipase activity was recovered after immobilization. Transesterification of Jatropha oil using nanobiocatalyst was optimized through RSM. The fuel properties of resultant biodiesel were under the range of ASTM D standards.